Nuclear Proliferation and International Order : Challenges to the Non-Proliferation Treaty. - Njølstad, Olav (Routledge Global Security Studies, 2010)
Examines the state of the nuclear non-proliferation regime and the issues it faces in the early 21st century. This book is suitable for students of nuclear proliferation, international security, war and conflict studies and IR in general.